Методика комплексної оцінки екологічних збитків від аварій на артскладах - Сидоренко, В.Л.; Азаров, С.І. (Екологічна безпека та природокористування, 2009)
In work brought estimation of the ecological damage at damages on military ammunition depots. The broughted methods of the calculation direct, indirect and social-ecological damage. Got given possible to use for motivation of the decisions on minimization ecological consequence damage.